The "do-not-resuscitate" order in palliative surgery: Ethical issues and a review on policy in Hong Kong. Issue 5 (October 2015) - Chan, Wing Lok
Abstract: A do-not-resuscitate (DNR) order, or "advance directive, " is commonly seen in the cases of palliative patients who express a wish to withhold specific resuscitative therapies in the event of a cardiac arrest. With recent technological advances, there are increasing numbers of palliative patients who undergo surgical interventions to treat their symptoms and discomfort. The decision to suspend DNR orders for palliative surgery is always a matter for debate. The present article describes a case and the ethical issues involved and gives some practical suggestions for those facing similar problems. We also review the latest DNR policy in Hong Kong.